Paternalistik dan patriarki dalam pemberdayaan perempuan pada pembangunan reformasi birokrasi - Harahap, Dony Aldise (Environmental, Social, Governance and Sustainable Business, 2024)
Background: Empowerment of women is still a concern both nationally and internationally. Women have not been maximally empowered because of a patriarchal, paternalistic culture and a narrow understanding of religion. Methods: This research was conducted using a qualitative approach. Research is supported by using secondary data, namely data that is not obtained directly from the field but is obtained from documents, for example journals, reference books, and regulations that support research. The data collected was tested for feasibility using source triangulation. The data that has been collected is analyzed using a descriptive approach. Findings: it is necessary to conduct research with the aim of analyzing paternalistic, patriarchal culture in empowering women in the development of bureaucratic reform. Conclusion: Research results: 1) gender equality will be obtained when paternalistic and paternalistic culture is not applied, but must apply equilibrium theory to be able to realize gender equality. 2) bureaucratic reform can be realized if gender equality is implemented, namely by prioritizing work professionalism to improve the quality of public services. 3) the implementation of gender equality is respect for women's rights in development, especially to realize bureaucratic reform.